2015
DOI: 10.4103/0976-237x.161885
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of clinical, hematological and systemic inflammatory markers in smokers and non-smokers with chronic periodontitis

Abstract: Context:Systemic conditions, especially chronic infections, have a direct impact on the general health and well-being of an individual. Similarly, the long-standing inflammatory changes seen during periodontitis have been associated with the altered diabetic control, preterm, low birth weight infants, and cardiovascular disease. Being a low-grade infection, the signs may not be as severe as seen in other systemic conditions, but they definitely cannot be ignored.Aims:The present study was designed to compare c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Additionally, another study showed consistently raised levels of IL-6, IL-1β and platelet derived growth factor in the alveolar cells that were stimulated by antigen present in tobacco leaves [ 29 ]. Also, an imbalance in the circulating levels of interleukins in tobacco smokers has been reported and studies have shown significantly increased levels of plasma IL-6 in smokers compared to non-smokers [ 7 , 8 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another study showed consistently raised levels of IL-6, IL-1β and platelet derived growth factor in the alveolar cells that were stimulated by antigen present in tobacco leaves [ 29 ]. Also, an imbalance in the circulating levels of interleukins in tobacco smokers has been reported and studies have shown significantly increased levels of plasma IL-6 in smokers compared to non-smokers [ 7 , 8 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking exerts an inflammatory effect on alveolar macrophages leading to the production of proinflammatory cytokines such as IL-6 and IL-1β [ 7 , 8 ]. However, although the harmful effects of tobacco smoke are avoided in smokeless tobacco products, the presence of nicotine in Naswar [ 2 ] could cause alterations in the levels of cytokines as nicotine has been to shown to exert immunosuppressive effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α level in serum act as diagnostic marker of periodontal disease in patients with Alzheimer disease (Kanakdande V). [ 69 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent research highlights their societal impact due to their high prevalence. Only 1% of patients have healthy periodontitis, and more than 16% of people are diagnosed with advanced periodontitis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%